“To Make Dark Heaven Light:” Transcending the Tragic in Sintang Dalisay - Alegre, Anne Nichole A. (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Directed by Ricardo Abad and choreographed by Matthew Santamaria, Sintang Dalisay—a Filipino adaptation of Shakespeare’s Romeo & Juliet—is often lauded for its use of the igal ethnic dance of the Sama-Badjau, a Muslim tribe located in the southern region of the Philippines. It depicts Rashiddin and Jamillia’s star-crossed love amidst a violent and ancient feud between their families. This paper discusses the process and product of interweaving performance traditions and cultures in Sintang Dalisay and how the adaptation transforms Shakespeare’s Romeo and Juliet from tragic to utopic. It does so in two aspects: the kinesthetic and the mythic. First, the use of the igal dance motif expresses and unearths the play’s inherently religious and celestial language. Second, the appropriation of Asian myths or beliefs—particularly of Chinese and Filipino origins—transforms and transcends the tragic ending of Romeo and Juliet’s deaths.